Intelligent Drying Rack Control System With Weather Condition Prediction Using Fuzzy Logic - Nur Darwisyah Faqihah, Lutfi (2023)
Most people's daily routines include washing and drying clothes. However, most of the people claimed that the process of drying up the clothes is the most challenging part due to the unpredictable weather in Malaysia. This project introduces an Intelligent Drying Rack Control System with weather condition prediction using Fuzzy logic that can automatically detect the presence of rain, sunlight and temperature, humidity. This drying rack system will be retrieved and pulled out when the system detects a change in surrounding weather. This project was developed to help people stay busy and focus on daily tasks outside and prevent their clothes from getting damp from the rain. The prototype model used hardware such as Arduino Uno, rain sensor, light sensor, DHT11 sensor and servo motor as actuator. Using Fuzzy logic showed that when it is cloudy, the sensor will pull the drying rack down to the roof, and when it gets sunny, it will be moved again. This initiative helps people manage their clothes when they are away from home, which reduces their stress and frees up their attention for other everyday duties.